ANALISIS FAKTOR KESIAPAN PERAWAT DALAM PRAKTIK KOLABORASI INTERPROFESIONAL DI RUMAH SAKIT PANTI NUGROHO YOGYAKARTA - Setya Widyastuti, Chatarina (Jurnal Media Ilmu Kesehatan, 2018)
Background: The best service in the patient cannot be separated from the collaboration practice among the professional health personal in providing the integrated service to the patient, including nurses. The ability to explain the knowledge, skills and role of nurses to other health professionals well is a competency that must be mastered by nurses as one of the members of an interprofessional team. Objective: find out the factors that influence nurse readiness in interprofessional collaboration practice (ICP) Methods: This study uses cross sectional design with total population of 63 nurses in hospital. Instrumen of this research used a valid and reliable quesioner. All data in this study analyzed univariate, bivariate and multivariate. Results: External and internal factors influence the readiness of interprofessional collaboration practice with p value 0.000. The most positive relationship is on social and interpersonal factors of consideration (correlation 0.739**). Ability variables age, education, social and interpersonal considerations, physical, organizational and institutional environments, behavior, intrapersonal and intellectual in explaining the variance of variables of readiness of interprofessional collaboration practice is 35%. Conclusion: Overall, the most factors that influence nurse readiness of interprofessional collaboration practice is social and interpersonal consideration (correlation 0.739**) Keywords: Nurse Readiness, Interprofessional Collaboration Practice, factors analysis